Can Trade Defence Instruments Address Social Issues? - Rumondang Puji Nur Suci*; Ernesto Simanungkalit (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
Trade has been linked to social issues in many instances, such as the promotion and protection of human rights, labour rights, and the preservation of the environment. This linkage can take the form of international cooperation between governments, or it can be unilateral in nature. In this paper, we will discuss the issue of using trade policy, in particular TDIs, to address social issues and climate change. We will start by having a general understanding of how to link trade policy to non-trade issues. We will then discuss the different approaches that governments have taken in linking trade with non-trade issues, including the rationale behind those decisions. Finally, we will reflect on the use of TDIs in addressing social issues, with a focus on the EU's anti-dumping and anti-subsidy regulations.This paper will contribute to the literature on the use of trade policy to address social issues by providing a comprehensive overview of the different approaches that have been taken, as well as the challenges and potential impact of using TDIs in this context.